An epidemiological study of Wilson's disease in the Republic of Ireland. Issue 3 (March 1993) - Reilly, M; Daly, L; Hutchinson, M
Abstract : In a population based study of the prevalence of Wilson's disease in the Republic of Ireland from 1970-89, 26 definite and probable cases were ascertained. The adjusted birth incidence rate was 17.0 per million live births (95% (confidence interval 9.9 to 27.2)) for the 20 year period 1950-69. The gene frequency was 0.41% (95% (confidence interval 0.31% to 0.52%) indicating that one in 122 of the population was a gene carrier. Allowing for a maximal degree of consanguinity, the gene frequency is reduced to 0.36% and the proportion of heterozygotes to one in 139 of the population. The consistency of the adjusted birth incidence rates over the decades 1950-59 and 1960-69 suggests a high degree of ascertainment of diagnosed cases of Wilson's disease.